Forming a Highly Active, Homogeneously Alloyed AuPt Co-catalyst Decoration on TiO2 Nanotubes Directly during Anodic Growth - Bian, Haidong; Nguyen, Nhat Truong; Yoo, Jeong Eun; Hejazi, Seyedsina; Mohajernia, Shiva; Müller, Julian; Spiecker, Erdmann; Tsuchiya, Hiroaki; Tomanec, Ondrej; Sanabria Arenas, Beatriz Eugenia; Zboril, Radek; Li, Yang Yang; et al. (ACS Applied Materials and Interfaces, 2018)
Au and Pt do not form homogeneous bulk alloys as they are thermodynamically not miscible. However, we show that anodic TiO2 nanotubes (NTs) can in-situ be uniformly decorated with homogeneous AuPt alloy nanoparticles (NPs) during their anodic growth. For this, a metallic Ti substrate containing low amounts of dissolved Au (0.1 at%) and Pt (0.1 at%) is used for anodizing. The matrix metal (Ti) is converted to oxide while at the oxide/metal interface direct noble metal particle formation and alloying of Au and Pt takes place; continuously these particles are then picked up by the growing nanotube wall. In our experiments the AuPt alloy NPs have an average size of 4.2 nm and, at the end of the anodic process, are regularly dispersed over the TiO2 nanotubes. These alloyed AuPt particles act as excellent co-catalyst in photocatalytic H2 generation - with a H2 production of 12.04 μL h-1 under solar light. This represents a strongly enhanced activity as compared with TiO2 NTs decorated with monometallic particles of Au (7 μL h-1) or Pt (9.96 μL h-1)
Keywords: anodization; photocatalysis; TiO2 nanotubes; AuPt alloy nanoparticle; H2 evolution